2018
DOI: 10.1021/acs.jpcc.7b11366
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Microwave Frequency and Power on Nanometal Growth

Abstract: The rapid heating rates (ΔT/δt) achieved in a microwave (MW) reactor has been shown to accelerate reaction rates due to the direct power absorbed (P abs ) into the reactants leading to faster kinetics. The P abs is proportional to the dielectric cross section of the materials as defined by the real (ε′) and imaginary (ε″) components. In a nanocrystal, the dielectric cross-section will be frequency dependent as well as size dependent. In this work, the frequency dependent growth of nickel nanocrystals at freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 67 publications
2
11
0
Order By: Relevance
“…Total IMFPs were reported with and without a correction for the effects of electron exchange that was based on Ashley's expression. [73] Figure 7e shows the IMFPs of Akkerman and Akkerman, with and without their exchange correction, together with our IMFPs from the FPA, SPA, SSPA, and SSPA*. We see that there is good agreement of the Akkerman and Akkerman IMFPs that include the exchange correction with our SSPA* results for energies between 40 eV and 10 keV; the RMS difference between them is 5.3%.…”
Section: Comparisons With Calculated Imfpssupporting
confidence: 51%
“…Total IMFPs were reported with and without a correction for the effects of electron exchange that was based on Ashley's expression. [73] Figure 7e shows the IMFPs of Akkerman and Akkerman, with and without their exchange correction, together with our IMFPs from the FPA, SPA, SSPA, and SSPA*. We see that there is good agreement of the Akkerman and Akkerman IMFPs that include the exchange correction with our SSPA* results for energies between 40 eV and 10 keV; the RMS difference between them is 5.3%.…”
Section: Comparisons With Calculated Imfpssupporting
confidence: 51%
“…Similarly, Strouse and col. showed that the increase in nanometal growth under microwave irradiation is a question of absorption of electromagnetic radiation and it is depended on the applied power . They considered that this effect was related to thermodynamics and not to non‐thermal microwave effects.…”
Section: Thermal Microwave Effectsmentioning
confidence: 99%
“…The suitable conductivity of the Au NPs layer provided the resonant interaction between the electrons and MWs, leading to the best heating property. For the isolated NPs system, there are only a few reports referring to the insight of the MW heating [30][31][32]. The supported NPs are often highly dispersed on the catalyst support that is also the isolated NPs system.…”
Section: Introductionmentioning
confidence: 99%